Taxonomy and redescription of the Fawn Antechinus, Antechinus bellus (Thomas) (Marsupialia: Dasyuridae) - Baker, Andrew M; Dyck, Steve Van (Zootaxa, 2013)
We provide a taxonomic redescription of the Fawn Antechinus, Antechinus bellus (Thomas). A. bellus is the only member of its genus to occur in Australia’s Northern Territory, where it can be found in savannah woodlands of the Top End. It is perhaps the most distinctive antechinus, and clearly distinguishable from the other 10 extant species of antechinus found in Australia: externally, A. bellus has pale body fur, white feet and large ears; A. bellus skulls have large auditory bullae and narrow interorbital width, while broadening abruptly at the molar row; mitochondrial and nuclear genes clearly dis-tinguish A. bellus from all congeners, phylogenetically positioning the Fawn Antechinus as sister to Queensland’s A. leo Van Dyck, 1980, with which it shares a curled supratragus of the external ear and a similar tropical latitudinal range.